2023
DOI: 10.3390/antiox12081628
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Oxidative Stress in Synaptic Dysfunction and Neuronal Cell Death in Alzheimer’s Disease

Germán Plascencia-Villa,
George Perry

Abstract: Alzheimer’s disease (AD) is a brain disorder that progressively undermines memory and thinking skills by affecting the hippocampus and entorhinal cortex. The main histopathological hallmarks of AD are the presence of abnormal protein aggregates (Aβ and tau), synaptic dysfunction, aberrant proteostasis, cytoskeletal abnormalities, altered energy homeostasis, DNA and RNA defects, inflammation, and neuronal cell death. However, oxidative stress or oxidative damage is also evident and commonly overlooked or consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 177 publications
0
10
0
Order By: Relevance
“…Oxidative stress, characterized by an imbalance between reactive oxygen species (ROS) production and the body's antioxidative defenses, plays a recognized and substantial role in the development and progression of AD [ 30 ]. This oxidative stress leads to cellular damage, including harm to neurons and neuronal membranes, thereby contributing to the observed cognitive decline in AD [ 31 ]. Polyphenols encompass a diverse group of compounds that are abundant in tea, particularly in green tea [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, characterized by an imbalance between reactive oxygen species (ROS) production and the body's antioxidative defenses, plays a recognized and substantial role in the development and progression of AD [ 30 ]. This oxidative stress leads to cellular damage, including harm to neurons and neuronal membranes, thereby contributing to the observed cognitive decline in AD [ 31 ]. Polyphenols encompass a diverse group of compounds that are abundant in tea, particularly in green tea [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is one of the main processes involved in AD pathogenesis [ 36 ]. In former studies, Behl and colleagues demonstrated that Aβ (25–35 and 1–40 peptides) caused increased H 2 O 2 levels and accumulation of lipid peroxides in primary cortical neurons, B12 and PC12 cells, affecting cell metabolism and survival [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress is linked to oxidative damage to proteins, nucleic acids, and lipids in susceptible cell populations, which ultimately results in neuronal death via many molecular processes. The development and testing of alternative therapeutic or preventive measures as possible or supplementary therapies for this debilitating neurodegenerative disease is enabled by the recognition of oxidative stress as a key component of AD. …”
Section: Introductionmentioning
confidence: 99%
“…The development and testing of alternative therapeutic or preventive measures as possible or supplementary therapies for this debilitating neurodegenerative disease is enabled by the recognition of oxidative stress as a key component of AD. 27 29 …”
Section: Introductionmentioning
confidence: 99%